PENGARUH KOMITMEN PROFESIONAL DAN SOSIALISASI ANTISIPATIF MAHASISWA AUDIT TERHADAP PERILAKU WHISTLEBLOWING - Fitri Yani Jalil (Esensi: Jurnal Bisnis dan Manajemen, 2014)
This study examines the anteceden of whistleblowing behavior by the professional commitment and anticipatory socialization student audit. It’s extend Elias (2008) and criticizes on the mismatch between the hypothesis with testing tools are used, so that the results can’t answer hypothetical appropriately. The used data is 104 of accounting students who have taken the course of auditing. Hypothesis testing used multiple regression test and t-test, with the previous factor analysis. The result indicates that professional commitment have significant effect on whistleblowing. The results also showed no significant difference to the level of anticipatory socialization respondents to whistleblowing. This study provides in addition to the audit literature by doing different test levels of professional commitment and anticipatory socialization student audit of whistleblowing behavior.DOI: 10.15408/ess.v4i1.1965